Patients' perceptions of nasopharyngeal aspiration in the emergency department of a teaching hospital in Hong Kong. Issue 1 (20th December 2006) - Wai, A K C; Kwok, W O; Chan, M S; Graham, C A; Rainer, T H
Abstract : Nasopharyngeal aspiration (NPA) is the preferred method for collecting specimens for viral culture in patients with respiratory tract infection. As virus identification may influence admission and treatment decisions, it is important to perform NPA in the emergency department. The test may be uncomfortable and poorly tolerated. This prospective study investigated patients' perceptions of NPA. Patients in the emergency department with upper respiratory tract infection undergoing NPA between 9 March 2005 and 12 August 2005 were included. 86 patients (mean (SD) age 47 (23) years; 49 women) were recruited. 22 (26%) patients complained that NPA was very uncomfortable, 59 (69%) reported that it was mildly uncomfortable and 5 (6%) patients reported no discomfort. On a 10-point scale, the median discomfort score was 4. 29 (34%) patients stated that NPA was more uncomfortable than blood taking, 19 (22%) patients felt that both were similar and 38 (44%) patients felt that NPA was less uncomfortable (p value not significant). NPA performed in the emergency department is well tolerated and should be considered in emergency departments when results may influence patient management.